The evolving molecular epidemiology of HIV type 1 among injecting drug users (IDUs) in Malaysia - Tee, K.K.; Saw, T.L.; Pon, C.K.; Kamarulzaman, A.; Ng, K.P. (2005)
Earlier studies in the 1990s indicate that human immunodeficiency virus type 1 (HIV-1) subtype B has been the predominant subtype among injecting drug users (IDUs) in Malaysia. More recent studies performed between 2003 and 2004, however, show a high prevalence of unique CRF01AE/B intersubtype recombinants among IDUs. To determine the subtype distribution among IDUs in Kuala Lumpur prior to the emergence of CRF01AE/B intersubtype recombinants, the gag-pol or the reverse transcriptase gene was sequenced from IDUs who were diagnosed as HIV positive between 1993 and 2002. Subtype B was present at 50.0 followed by CRF01AE/B recombinant at 41.7, with more CRF01AE/B recombinants detected between 2000 and 2002. All CRF01AE/B recombinants shared similar recombination patterns. Interestingly, we found that this potential new candidate of circulating recombinant form (CRF) could have emerged as early as the mid-1990s. The results showed evidence of changing HIV-1 molecular epidemiology toward the predominance of CRF01AE/B intersubtype recombinants among IDUs in Kuala Lumpur.